STUDENTS’ BEHAVIOUR OF INDISCIPLINE SYNDROME IN TEACHING AND LEARNING PROCESS - Blegur, Jusuf (Universitas Pendidikan Indonesia, 2017)
This study reported the discovery and identification of behavioral syndrome of students’ indiscipline in teaching and learning process. For this purpose, researcher used qualitative approach of phenomenology. The study involved 9 subjects determined by purposive sampling for the phenomenon of indiscipline were more dominated by those subjects. Four techniques have been used to collect the data: participation-observation, in-depth interviews, field notes, and documentation. The results indicated that the behavioral syndrome of indiscipline is influenced by premature (imature) self-concept, determination of multidimensional environment, keeping and building a societal relationship in communities, as well as teachers’ attitude and behavior as a direct model. Therefore, teachers should give the exemplary cognition, affection, psychomotor, as well as should be truthful and orderly socially so that the students’ behaviour of indiscipline can be reduced to a good quality of learning.